Detection Moleculer Of Putative 18S rRNA Gen Protozoa Trichodina sp. Infected Larvae Gurami (Osphronemus gouramy L) in Balai Benih Ikan Kutasari Purbalingga Central Java - Rokhmani, Rokhmani; Wahyono, Daniel Joko; Mulyani, Lilis (Fakultas Biologi Universitas Jenderal Soedirman, 2021)
Trichodina spp. are ectoparasitic pathogens of ciliata group that commonly infect both freshwater and marine fish, including gouramy fish. As a result of infection of Trichodina spp. this will lead to inhibition of fish growth and decreased fish production, resulting in low fish selling value. The rate of occurrence of Trichodina spp. that infects gurami can reach 100%. Research has been conducted to determine which one Trichodina spp. Protozoa that infects the gouramy seeds of BBI (Fish Seed Center) Kutasari Purbalingga following detection of 18S RNA gene. Gene detection method used in this research is Polymerase Chain Reaction (PCR) is a technique of DNA synthesis and amplification in vitro. This research is done following these methodes: (1) sampling of Gurami fish with purposive sampling which obtained from BBI Kutasari Purbalingga, (2) isolation of Trichodina spp., (3). Preparation of Trichodina spp. sample and its identification, and (4). Molecular character obervation following detection of 18S rRNA gene. This study obtained 10% percentage of detection of 18S rRNA genes of the species of Trichodina paraheterodentata that infect on the gouramy fish of Purbalingga. The percentage rate of detection of these genes is low when compared with the results of the detection of 18S rRNA Trichodina paraheterodentata gene that infects gouramy fish in Banjarnegara.